2007
DOI: 10.1080/13682820601170102
|View full text |Cite
|
Sign up to set email alerts
|

Prosody and its relationship to language in school‐aged children with high‐functioning autism

Abstract: Marion (2005) Prosody and its relationship to language in school-aged children with high-functioning autism. Accessed from:http://eresearch.qmu.ac.uk/141/ Repository Use PolicyThe full-text may be used and/or reproduced, and given to third parties for personal research or study, educational or not-for-profit purposes providing that:• The full-text is not changed in any way • A full bibliographic reference is made • A hyperlink is given to the original metadata page in eResearch eResearch policies on access an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
131
1
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(149 citation statements)
references
References 47 publications
5
131
1
7
Order By: Relevance
“…However, SLI and TD children had very high recognition rates for the "Rising" intonation whereas both AD and PDD-NOS performed significantly worse. This result is coherent with studies that showed PDD children have more difficulties at imitating questions than statements [24] as well as short and long prosodic items [25], [27]. As pragmatic prosody was strongly conveyed by the "Rising" intonation due to the short questions, it is not surprising that such intonation recognition differences were found between SLI and the PDDs.…”
Section: E E E P R O O F P R I N T V E R S I O Nsupporting
confidence: 89%
See 1 more Smart Citation
“…However, SLI and TD children had very high recognition rates for the "Rising" intonation whereas both AD and PDD-NOS performed significantly worse. This result is coherent with studies that showed PDD children have more difficulties at imitating questions than statements [24] as well as short and long prosodic items [25], [27]. As pragmatic prosody was strongly conveyed by the "Rising" intonation due to the short questions, it is not surprising that such intonation recognition differences were found between SLI and the PDDs.…”
Section: E E E P R O O F P R I N T V E R S I O Nsupporting
confidence: 89%
“…Paul et al [3] found no difference between AD and TD children in the use of intonation to distinguish questions and statements. Peppé and McCann [25] observed a tendency for AD subjects to utter a sentence that sounds like a question when a statement was appropriate. Le Normand et al [26] found that children with AD produced more words with flat contours than typically developing children.…”
Section: A Prosodymentioning
confidence: 99%
“…Appropriate voice F 0 modulation is crucial for successful social interaction as it imparts information about the subject's state of mind, emotion, or intent. Thus, due to the abnormal prosody of speech in children with ASD, conversation with peers is often strained (Paul et al 2005b;McCann et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is known that children with ASD have at least some prosodic impairment and that the use of prosody to convey affect and phrase level stress are abilities harder to master (McCann, Peppé, Gibbon, O'Hare, & Rutherford, 2007). Despite previous studies, research has not yet provided a consistent characterization or typology of these prosodic disordered patterns and studies have not captured the extent of prosodic impairments in ASD.…”
mentioning
confidence: 99%